Growth, mortality and yield per recruit of Johnieops sina (Cuvier) from Mumbai, India - Telvekar, Prashanth A; Biradar, R S; Chakraborty, S K; Jaisawar, A K; Rathod, Rajeev (Indian Journal of Fisheries, 2011)
The growth, mortality and yield-per-recruit of sin croaker Johnieops sina is reported based on the data collected during September 2003 to May 2005 from Mumbai. The asymptotic length (Lâˆž) was calculated as 258 mm and growth coefficient (K) as 0.91yr-1. The Z, M and F were estimated as 5.25, 1.35 and 3.90 respectively. The Z/K of 5.76 shows that the species is subjected to high levels of exploitation. The yield isopleth diagram shows that optimum yield can be obtained at Lc/Lâˆž value of 0.5 and E of 0.6. This shows that the fish belongs to quadrant â€œ D â€ of Yield isopleth diagram where small fish are caught at high effort level. Increase in mesh size coupled with decrease in fishing effort is suggested for sustainable management of this resource.